Interaksi Adat, Agama, dan Lembaga Budaya dalam Pelestarian Kesenian Tradisional: Studi Padepokan Cipto Mudho Laras di Kabupaten Kediri, Jawa Timur (2000–2024) - Yasa, Wisnu Gillang Permana; Ida Ayu Wirasmini Sidemen; Anak Agung Ayu Rai Wahyuni (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This article examines the interaction between customary values, religious values, and cultural institutions in the dynamics of traditional arts preservation through a case study of Padepokan Cipto Mudho Laras in Kediri Regency, East Java, during the period 2000–2024. Traditional Kediri arts, known as Seni Kediren, face serious pressure from modernization and the shifting interests of younger generations, threatening their continuity. This study employs a historical method with a microhistory approach, encompassing the stages of heuristics, source criticism, interpretation, and historiography. Data were collected through in-depth interviews, field observation, and documentary study. The findings reveal three main conclusions: first, Padepokan Cipto Mudho Laras was founded in 2000 as a historical response to the stagnation of Wayang Krucil Gagrag Kediren and as a tribute to artistic ancestors; second, the padepokan serves as a dynamic space for interaction between Javanese customary values and Kejawen-Islamic teachings, manifested through three core activities—traditional arts preservation, arts education, and arts development or revitalization; third, the padepokan has significant socio-cultural implications for local communities and regional government policy, including the strengthening of social cohesion, increased cultural participation, and the promotion of community-based preservation policies. This study affirms that Padepokan Cipto Mudho Laras functions not merely as a preservation institution but as an adaptive agent of cultural transformation.